BFGF and JAGGED1 regulate alkaline phosphatase expression and mineralization in dental tissue‐derived mesenchymal stem cells. Issue 11 (13th September 2013) - Osathanon, Thanaphum; Nowwarote, Nunthawan; Manokawinchoke, Jeeranan; Pavasant, Prasit
ABSTRACT Basic fibroblast growth factor (bFGF) and Notch signaling play critical roles in various cell behaviors. Here, we investigated the influence of bFGF and Notch signaling in alkaline phosphatase (ALP) expression and mineralization process in human periodontal ligament‐derived mesenchymal stem cells (PDLSCs) and stem cells isolated from human exfoliated deciduous teeth (SHEDs). PDLSCs and SHEDs were cultured in osteogenic medium supplemented with bFGF or on the immobilized Notch ligands, JAGGED1. The ALP mRNA and protein expression were measured by quantitative reverse transcriptase polymerase chain reaction and enzymatic activity assay, respectively. Mineral deposition was determined using alizarin red S staining. The results showed that the addition of bFGF resulted in the decrease of ALP mRNA expression and enzymatic activity. In addition, the attenuation of mineralization was noted. These phenomenons were blocked by the addition of a fibroblast growth factor receptor inhibitor (SU5402) or a MEK inhibitor (PD98059). Interestingly, bFGF supplementation also decreased the Notch signaling component mRNA levels. Thus, to evaluate effect of Notch signaling in mineralization process, PDLSCs and SHEDs were exposed to JAGGED1 modified surface. The ALP mRNA and protein expression were significantly upregulated and the mineral deposition was markedly increased. These results could be reversed by the addition of a γ‐secretase inhibitor. In addition, bFGF could attenuate the Notch‐signaling‐induced mineralization in both PDLSCs and SHEDs. These results suggest that mineralization was enhanced by Notch signaling but attenuated by bFGF signaling. This knowledge can be further utilized to control PDLSCs and SHEDs mineralization for tissue regeneration purpose. J. Cell. Biochem. 114: 2551–2561, 2013. © 2013 Wiley Periodicals, Inc.